The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12283-011-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Embedded programming and real-time signal processing of swimming strokes

Abstract: The research outlined in this paper was conducted to allow real-time processing, transmission and presentation of data to swimming coaches and subsequently their swimmers in a training environment, focused on providing information relevant to strokes in free swimming. This was achieved using a wearable wireless sensor and embedded programming techniques, using accelerations involved in the swimming stroke to provide relevant features for coaches. Current methods used do not offer real-time response to coaches,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 23 publications
4
70
1
Order By: Relevance
“…Recently, wearable inertial-magnetic measurement units (IMMUs) have been used (Magalhaes, Vannozzi, Gatta, & Fantozzi, 2015). Initially, stroke rate, stroke phases analysis and discrimination among different swimming styles were performed (Dadashi et al, 2013;Le Sage et al, 2011;Ohgi, Ichikawa, Homma, & Miyaji, 2003). Subsequently, the velocity, attitude and position of the swimmer were estimated to have specific performance indicators for the whole length of the swimming pool (Dadashi, Crettenand, Millet, & Aminian, 2012;Stamm, James, & Thiel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, wearable inertial-magnetic measurement units (IMMUs) have been used (Magalhaes, Vannozzi, Gatta, & Fantozzi, 2015). Initially, stroke rate, stroke phases analysis and discrimination among different swimming styles were performed (Dadashi et al, 2013;Le Sage et al, 2011;Ohgi, Ichikawa, Homma, & Miyaji, 2003). Subsequently, the velocity, attitude and position of the swimmer were estimated to have specific performance indicators for the whole length of the swimming pool (Dadashi, Crettenand, Millet, & Aminian, 2012;Stamm, James, & Thiel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that it took approximately seven and a half hours to carry out manual digitization of a relatively small amount of footage, involving ten swimmers performing three dives each. 70 Magalhaes, et al 71 also cite another example whereby it took 27 hours to digitize footage of four separate stroke cycles for one swimmer, involving images from six cameras, 19 anatomical landmarks and 1,620 frames in total.…”
Section: 69mentioning
confidence: 99%
“…Collection of performance parameters during training rather than competition allows the use of alternative measurement techniques such as wireless accelerometers or inertial sensors [8][9][10]. These systems offer real-time feedback and valuable velocity data of the swimmers, but unfortunately are not able to be used in competitive environments.…”
Section: Introductionmentioning
confidence: 99%